Kekerasan dalam Rumah Tangga Perspektif Fikih - La Jamaa (AHKAM : Jurnal Ilmu Syariah, 2013)
Abstract: Domestic Violence in Fiqh Perspective. This study intends to explore the views of Islamic Jurists against domestic violence and   their perspective in preventing the violence in the house hold. According to Islamic jurisprudence, domestic violence committed by a husband to his wife is against law. The violence itself can be implemented by many forms such as physical, psychological, sexual, as well as economic violence. In order to give lesson, a husband is allowed to beat his wife, if only not hurting her. On the other hand, a husband is obliged to fulfill economical, pschychological and sexual needs of his wife. As a preventive measure, jurisprudence offer measures, such as choosing a devout husband or wife to be maried and preventing children become a target of domestic violence.Keywords: islamic jurisprudence, nushūz, domestic violenceAbstrak: Kekerasan dalam Rumah Tangga Perspektif Fikih. Studi ini bermaksud menggali pandangan ulama fikih terhadap kekerasan dalam rumah tangga dan bagaimana upaya preventif dari tindak kekerasan dalam rumah tangga tersebut. Menurut fikih Islam, kekerasan dalam rumah tangga yang dilakukan suami kepada istri adalah haram hukumnya, baik kekerasan fisik, psikis, seksual, maupun ekonomi. Karena itu dispensasi suami memukul istri yang nusyu hanyalah upaya edukatif namun tidak boleh menyakiti istri. Suami diharamkan mengancam, mengabaikan nafkah batin, nafkah lahiriah, serta kebutuhan seksual istrinya. Sebagai langkah preventif, fikih menawarkan langkah- langkah, antara lain memilih calon suami atau istri yang taat beragama dan menghindarkan anak dari suasana kekerasan dalam rumah tangga.Kata Kunci: fikih Islam, nusyu, kekerasan dalam rumah tangga